Optimasi Aktivitas Antioksidan Minuman Herbal Celup Berbahan Bunga Telang dan Serai - Marni Jayanti; Sulistyo Prabowo; Krishna Purnawan Candra; Aswita Emmawati (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2025)
Butterfly pea flowers and lemongrass are developed as functional herbal drinks because have antioxidant benefits. The combination of the two was innovated herbal drink packaged in tea bags, so it was necessary to create an optimal formula. This study aims to measure on the response antioxidant activity and total flavonoid content from the combination of butterfly pea flower(A), lemongrass(B), and drying time(C). Additionally, the study to obtain the optimal formulation and validated its antioxidant activity, total flavonoid content, as physical characteristics (pH and color intensity) and organoleptic characteristics herbal beverage combination of butterfly pea flower and lemongrass packaged in tea bag. The research utilized a Box-Behnken design with variable combinations: (A) 0.50–1.00 g, (B) 1.00–1.50 g, and (C) 23–25 hours (using an oven drying method at approximately 55 °C). The results indicated that variables A, B, C, their interactions (AB, AC, and BC), had no significant effect (p>0.05) on antioxidant activity. However, the total flavonoid content was influenced differently. Variables B, C, and their interaction (BC) had a significant effect (p<0.05) on total flavonoid content, while other variables did not show significant effects. The optimal formulation for the herbal beverage (200 mL) is (A) 0.50 g, (B) 1.22 g, and (C) 24 hours. This formulation yielded a validated IC50 antioxidant activity of 23.36±6.62 ppm, a total flavonoid content of 255.07±25.10 mg QE/L, and satisfactory physical and organoleptic characteristics aligning with standards from previous research. The optimized formulation is recommended as a functional beverage due to its flavonoid, which provides potential antioxidant benefits for the body.